CuO/ZnO Nanocomposite Biosynthesis Approach Using Eucalyptus Leaves for Photodegradation of Tetracycline - S. Ameer, Marwa; A. Atiya, Mohammed; Hassan, Ahmed K.; Shakorfow, Abdelmalik Milad; Al Mhanna, Najah (Al-Khwarizmi Engineering Journal, 2024)
In this study, the photocatalytic degradation of tetracycline (TC), which is responsible for water pollution, was investigated in an aqueous solution by using two types of nanoparticles (NPs) based on green synthesis of ZnO NPs and CuO NPs as photocatalysts. Eucalyptus plant extract was chosen as a good reductant and capping agent because of its cost-effectiveness, nontoxic characteristics and ease of usage. Different molar ratios of Cu:Zn (1:3, 1:6, 1:9 and 1:12) were prepared, and then these ratios were evaluated to select the effective ratio for removing TC. The 1:6 ratio demonstrated the best photocatalytic performance, degrading 72.15% of TC at the ZnO/CuO nanocomposite (NC) dose of 0.5 g/L, an initial concentration of 10 mg/L, pH 7, an agitation speed of 300 rpm, a temperature of 25 °C, UV intensities of 15 W/m2 and a contact time of 180 min. The synthesis of NCs was characterised using different analysis methods. CuO/ZnO characteristics were investigated using several analytical techniques, including FTIR, FESEM, EDAX, AFM, BET and zeta potential analysis. The NP’s structure, morphology, thermal behaviour, chemical composition and optical properties were analysed. The FESEM images verified that the (1:6) CuO/ZnO NPs calcined and not calcined, with sizes of 13.92 and 26.73 nm, respectively, were crystalline and spherical. The quantity of TC degradation by metal oxide NCs was investigated using UV–Vis spectroscopy. This method is sustainable and environmentally benign because it synthesises both NPs from plant sources. These hybrid nanoparticles may be used to treat other pharmaceuticals that are hazardous to reduce pollution in water.